A monoclonal antibody-based immunoassay to measure the antibody response against the repeat region of the circumsporozoite protein of Plasmodium falciparum. (December 2016) - Radin, Kristina; Clement, Frederic; Jongert, Erik; Sterckx, Yann; Ockenhouse, Christian; Regules, Jason; Lemiale, Franck; Leroux-Roels, Geert
Abstract Background The malaria vaccine candidate RTS, S/AS01 (GSK Vaccines) induces high IgG concentration against the circumsporozoite protein (CSP) ofPlasmodium falciparum . In human vaccine recipients circulating anti-CSP antibody concentrations are associated with protection against infection but appear not to be the correlate of protection. However, in a humanized mouse model of malaria infection prophylactic administration of a human monoclonal antibody (MAL1C), derived from a RTS, S/AS01-immunized volunteer, directed against the CSP repeat region, conveyed full protection in a dose-dependent manner suggesting that antibodies alone are able to preventP. falciparum infection when present in sufficiently high concentrations. A competition ELISA was developed to measure the presence of MAL1C-like antibodies in polyclonal sera from RTS, S/AS01 vaccine recipients and study their possible contribution to protection against infection. Results MAL1C-like antibodies present in polyclonal vaccine-induced sera were evaluated for their ability to compete with biotinylated monoclonal antibody MAL1C for binding sites on the capture antigen consisting of the recombinant protein encompassing 32 NANP repeats of CSP (R32LR). Serum samples were taken at different time points from participants in two RTS, S/AS01 vaccine studies (NCT01366534 and NCT01857869). Vaccine-induced protection status of the study participants was determined based on the outcome of experimental challenge with infected mosquito bites after vaccination. Optimal conditions were established to reliably detect MAL1C-like antibodies in polyclonal sera. Polyclonal anti-CSP antibodies and MAL1C-like antibody content were measured in 276 serum samples from RTS, S/AS01 vaccine recipients using the standard ELISA and MAL-1C competition ELISA, respectively. A strong correlation was observed between the results from these assays. However, no correlation was found between the results of either assay and protection against infection. Conclusions The competition ELISA to measure MAL1C-like antibodies in polyclonal sera from RTS, S/AS01 vaccine recipients was robust and reliable but did not reveal the elusive correlate of protection.